2017
DOI: 10.1016/j.stemcr.2017.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Expansion and Purification Are Critical for the Therapeutic Application of Pluripotent Stem Cell-Derived Myogenic Progenitors

Abstract: SummaryRecent reports have documented the differentiation of human pluripotent stem cells toward the skeletal myogenic lineage using transgene- and cell purification-free approaches. Although these protocols generate myocytes, they have not demonstrated scalability, safety, and in vivo engraftment, which are key aspects for their future clinical application. Here we recapitulate one prominent protocol, and show that it gives rise to a heterogeneous cell population containing myocytes and other cell types. Upon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 35 publications
2
73
1
Order By: Relevance
“…These efforts employed by tuning major signaling pathways governing stem cell differentiation toward mesoderm and muscle, such as WNT, BMP, and transforming growth factor β (TGF-β) (Barberi et al, 2007; Borchin et al, 2013; Caron et al, 2016; Chal et al, 2015; Hicks et al, 2018; Shelton et al, 2014; Xi et al, 2017; Xu et al, 2013). Although these methods were successful in inducing skeletal myogenesis, parallel generation of unwanted cell types hindered the purity of the myogenic cells, as recently reported by our collaborators (Kim et al, 2017). Even in the most recent methods (Hicks et al, 2018; Shelton et al, 2016), the need for a long-term culture (up to 50 days) and associated difficulties (such as mixed cultures and difficulties in maintenance and harvest) are among major obstacles.…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…These efforts employed by tuning major signaling pathways governing stem cell differentiation toward mesoderm and muscle, such as WNT, BMP, and transforming growth factor β (TGF-β) (Barberi et al, 2007; Borchin et al, 2013; Caron et al, 2016; Chal et al, 2015; Hicks et al, 2018; Shelton et al, 2014; Xi et al, 2017; Xu et al, 2013). Although these methods were successful in inducing skeletal myogenesis, parallel generation of unwanted cell types hindered the purity of the myogenic cells, as recently reported by our collaborators (Kim et al, 2017). Even in the most recent methods (Hicks et al, 2018; Shelton et al, 2016), the need for a long-term culture (up to 50 days) and associated difficulties (such as mixed cultures and difficulties in maintenance and harvest) are among major obstacles.…”
Section: Introductionmentioning
confidence: 70%
“…So far, previous studies have suffered from the lack of prospective readout to guide the differentiation path and subsequently purify myogenic progenitors and therefore carrying unwanted or mixed cell populations (Kim et al, 2017). Here, we have taken the advantage of generating a double-reporter hESC line for muscle lineage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it would be expected that cells capable of differentiating in vitro are able to fuse to existing myofibers in vivo, the cell-to-cell interactions occurring in the petri dish combined with a still heterogeneous composition of the population under investigation (particularly in the case of protocols not involving cell-sorting) represent a limit for the direct translation of these PS cell-derived myogenic cell preparations. Indeed, this is supported by recent findings demonstrating the need of cell-purification strategies and robust lineage commitment for the successful engraftment of muscle progenitors derived using directed differentiation of PS cells [138]. …”
Section: Myogenic Differentiation Of Pluripotent Cells Through Modmentioning
confidence: 65%
“…An obvious example of the variation among lines is the requirement of variable concentration of the GSK3i inhibitor for mesoderm induction [124]. In the case of skeletal myogenesis, it has been shown that human PS cell lines display a variable capability to differentiate using a chemically defined protocol, thus implying the need of further improvements before the generalization of current protocols [138]. As in the case of maturation, detailed analysis of the epigenetic mechanisms behind cell differentiation will definitively help to understand why some PS cell lines are more permissive than others.…”
Section: Current Issues and Future Applications Of Pluripotent Stementioning
confidence: 99%